2013
DOI: 10.1364/oe.21.015728
|View full text |Cite
|
Sign up to set email alerts
|

Yellow-to-orange emission from Bi^2+-doped RF_2 (R = Ca and Sr) phosphors

Abstract: RF2:Bi (R = Ca and Sr) phosphors were synthesized by solid state reaction method in air and their luminescence properties were investigated. Broad yellow-to-orange emissions peaking at ~550 nm (CaF2:Bi) and ~600 nm (SrF2:Bi) were observed under ~260 nm excitation. The emission centers inRF2:Bi (R = Ca and Sr) phosphors are Bi2+ ions, and the excitation and emission bands of RF2:Bi (R = Ca and Sr) phosphors can be attributed to 2P 1/2 → 2S 1/2 and 2P 3/2(1) → 2P 1/2 transitions of Bi2+ ions, respectively. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…In 1994, the red emission of Bi-doped SrB 4 O 7 was explained by Blasse et al [105] as due to the divalent Bi 2+ based on the similarity of luminescence characteristics with isoelectronic Pb + [209] and Tl 0 [210,211] centers. In the same year, Bi 2+ luminescence was briefly reported in alkali earth sulfates [212], followed by reports dealing with Bi 2+ in crystalline hosts of Me 2+ BPO 5 (Me = Ca, Sr, Ba) [213], BaB 8 O 13 [214], BaSO 4 [215], Sr 2 P 2 O 7 [216], Ba 2 P 2 O 7 [106], MeF 2 (Me = Ca, Sr) [217], and CaAl 12 O 19 [218].…”
Section: The Bi 2+ Bi + and Bi 0 Emission Centersmentioning
confidence: 99%
“…In 1994, the red emission of Bi-doped SrB 4 O 7 was explained by Blasse et al [105] as due to the divalent Bi 2+ based on the similarity of luminescence characteristics with isoelectronic Pb + [209] and Tl 0 [210,211] centers. In the same year, Bi 2+ luminescence was briefly reported in alkali earth sulfates [212], followed by reports dealing with Bi 2+ in crystalline hosts of Me 2+ BPO 5 (Me = Ca, Sr, Ba) [213], BaB 8 O 13 [214], BaSO 4 [215], Sr 2 P 2 O 7 [216], Ba 2 P 2 O 7 [106], MeF 2 (Me = Ca, Sr) [217], and CaAl 12 O 19 [218].…”
Section: The Bi 2+ Bi + and Bi 0 Emission Centersmentioning
confidence: 99%
“…The emission changed mainly in the blue region to the orange red region with an increase in beam voltage. The blue and orange emissions were reported by many authors as a characteristic emission from Bi 3+ and Bi 2+ respectively [57,58]. A simplified energy level diagram, with the respected obtained color images, from Reference [48], is given in Figure 14.…”
Section: Resultsmentioning
confidence: 96%
“…The Bi 2+ ion has recently motivated a new line of approach in the search of new red phosphors for energy efficient solid-state lighting devices. [1][2][3][4][5][6][7] This line finds its grounds on the earlier work of Blasse et al, 8 who considered the rarely reported divalent bismuth species to be responsible for the red-orange luminescence of bismuth activated SrB 4 O 7 . By extension, Bi 2+ was assumed to cause the red luminescence of bismuth activated alkaline earth sulfates already reported in 1886 by Lecoq de Boisbaudran 9 and of bismuth activated phosphates reported in 1949 by Kro ¨ger et al 10 (cf.…”
Section: Introductionmentioning
confidence: 77%